Rectal Anticonvulsant Therapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The use of rectally administered antiepileptic drugs (AEDs) is reviewed by experts from the College of Pharmacy and Division of Pediatric Neurology, University of Minnesota, Minneapolis, Minn.